2021
DOI: 10.3390/brainsci11101317
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Function, Behaviour and Cognition in a Cohort of Children with Down Syndrome

Abstract: Objective: To describe the sleep problems experienced by children with Down syndrome attending a tertiary sleep clinic and relationship with behaviour, function and cognition. Methods: Data were collected from children with Down syndrome aged 3–18 years old. Carers completed the Abbreviated Child Sleep Habits Questionnaire, Child Behaviour Checklist and Life-Habits Questionnaire at enrolment. Cognitive assessment (Stanford-Binet 5) was undertaken by a trained psychologist. Children received management for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…We identified that daytime sleepiness as assessed by the ESS‐CHAD, behaviour as assessed by the CBCL, or daily functioning skills as assessed by the ABAS‐II did not change in either group at follow‐up. Our findings are supported by a previous study that also reported no association between sleep problems (snoring, sleep study confirmed OSA, or non‐respiratory sleep problems) and parent reported behavioural problems assessed by the CBCL, functional impairments assessed by the Life Habits Questionnaire or intellectual performance assessed by the Stanford‐Binet Intelligence Scales in children with DS (Chawla et al, 2021). Additionally, actigraphic sleep parameters assessing sleep duration and quality have been found to be not related to cognitive task performance in children with DS, whereas they were in typically developing children (Ashworth et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We identified that daytime sleepiness as assessed by the ESS‐CHAD, behaviour as assessed by the CBCL, or daily functioning skills as assessed by the ABAS‐II did not change in either group at follow‐up. Our findings are supported by a previous study that also reported no association between sleep problems (snoring, sleep study confirmed OSA, or non‐respiratory sleep problems) and parent reported behavioural problems assessed by the CBCL, functional impairments assessed by the Life Habits Questionnaire or intellectual performance assessed by the Stanford‐Binet Intelligence Scales in children with DS (Chawla et al, 2021). Additionally, actigraphic sleep parameters assessing sleep duration and quality have been found to be not related to cognitive task performance in children with DS, whereas they were in typically developing children (Ashworth et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…We also assessed aspects of daytime behaviour and functioning with parental questionnaires. We identified that daytime sleepiness as Scales in children with DS (Chawla et al, 2021). Additionally, actigraphic sleep parameters assessing sleep duration and quality have been found to be not related to cognitive task performance in children with DS, whereas they were in typically developing children (Ashworth et al, 2015).…”
Section: Associations Between Actigraphic Sleep Variables and Questio...mentioning
confidence: 95%
“…Other significant associations were also reported in the accomplishment of responsibilities, relationships, community life, school, mealtimes, fitness and personal care (Churchill et al, 2015). However, Chawla, Bernard, et al (2021) found no relationship between sleep and cognition, functional ability or behaviour. Suggesting that these problems are not solely driven by sleep issues, with confounding variables such as physical problems and pain potentially affecting both sleep and behaviour (Chow et al, 2020; Esbensen et al, 2021).…”
Section: Resultsmentioning
confidence: 98%
“…In spite of the crucial role of sleep in pediatric age, especially for population with DS, very few studies specifically investigated the distribution of sleep difficulties and their behavioral correlates in preschool-age children with DS. On the other hand, the studies that investigated sleep problems in preschoolers with DS included wide age ranges ( Levanon et al, 1999 ; Carter et al, 2009 ; Nisbet et al, 2014 ; Bassell et al, 2015 ; Anand et al, 2021 ; Chawla et al, 2021 ; Fucà et al, 2021 ; Kose et al, 2021 ). Moreover, studies focusing on preschoolers with DS were conducted on small sample sizes ( Edgin et al, 2015 ; Joyce and Dimitriou, 2017 ; D’Souza et al, 2020 ; Lukowski et al, 2020 ; Arias-Trejo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%